Pola Interaksi Masyarakat dan Dampaknya Terhadap Resensi Ibukota Kecamatan - Tihurua, Jija Rahma; Aksa, Kamran; Idris Taking, Muhammad (Journal of Urban Planning Studies, 2024)
This study aims to identify how the pattern of community interaction and determine the impact of community interaction that affects the review of the capital of Salahutu District. The results of the analysis show that the picture or pattern of community interaction in the Salahutu District area occurs in several aspects, namely Social Conditions, Social Order, Belief Systems (Religious Tolerance), Social Norms (Customs) and Social Renewal (Social Interaction) between communities in villages. Analysis of the impact of community interaction on the review of the capital of Salahutu District found that the pattern of community interaction had a positive and negative impact on the capital of Salahutu District (Tulehu). The suggestion in this study is that in order not to shift local cultural values (local wisdom), the local government through the tourism office and social office of Central Maluku Regency continues to socialize programs based on local wisdom, for example by making the Salahutu cultural festival once a year. The preparation of the Regional Spatial Plan (RTRW) of Central Maluku Regency should consider the spatial structure of the sub-districts in the Central Maluku Regency area and be synchronized with the diversity of local wisdom of the community. This is so that the resulting spatial planning products are also based on local wisdom.